FUTURE WATER REQUIREMENTS FOR RICE IRRIGATION IN THE PARDO RIVER BASIN (BRAZIL) - Helfer, Fernanda; Louzada, José Antônio (IRRIGA, 2018)
1 ABSTRACT The objective of this research was to estimate the future water requirements for rice paddy irrigation in the Pardo River Basin (Brazil) taking into account the changes in cultivation systems that are likely to occur in the near future in that region. After identifying the major trends in the rice cultivation systems, different scenarios were set and the water requirements for these scenarios were estimated using mathematical modelling and geoprocessing techniques. Census data indicate that the rice-growing area in the Pardo River Basin is expanding. However, the use of water per hectare is decreasing, as a result of increasing water use efficiency. The main agent behind this higher efficiency is land-levelling, which allows for a reduced volume of water required for flooding the paddies. Despite this improvement however, the overall water demands in future scenarios will still be greater than the current demands due to the expansion of the farmed area. However, these demands can be minimized if land-levelling is adopted more intensively across the entire Basin. Otherwise, there will be a need for either controlling the expansion of the rice-growing area, or increasing water availability through construction of additional reservoirs to minimize potential conflict amongst water users in the near future. Keywords: rice, water requirements, irrigation, GIS, water availability demand